Study of skin anti-ageing and anti-inflammatory effects of dihydroquercetin, natural triterpenoinds, and their synthetic derivatives - Lee, Chan Woo; Park, Nok Hyun; Kim, Jin Woong; Um, Byung Hun; Shpatov, A. V.; Shults, E. E.; Sorokina, I. V.; Popov, S. A. (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2012)
Accessible triterpenoids of ursane and lupane series, the flavonoid dihydroquercetin and their synthetic derivatives with polar substituents were tested in vitro for inhibition of collagenase 1 (MMP-1) in UVB irradiation assay. Ursolic acid and uvaol disuccinate were the most active inhibitors in the ursane series. In the lupane series, the best inhibition was manifested by carboxymethyl ester of betulonic acid and betulin succinates. Down- regulation of MMP-1 by dihydroquercetin and its synthetic derivatives surpassed the activity of a standard (retinoic acid).